2017
DOI: 10.3390/molecules22071107
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Modification of Clinoptilolite

Abstract: Clinoptilolite is a natural mineral with exceptional physical characteristics resulting from its special crystal structure, mainstreamed into a large zeolite group called heulandites. An overall view of the research related to the synthesis, modification and application of synthetic clinoptilolite is presented. A single phase of clinoptilolite can be hydrothermally synthesized for 1–10 days in an autoclave from various silica, alumina, and alkali sources with initial Si/Al ratio from 3.0 to 5.0 at a temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 78 publications
3
31
0
2
Order By: Relevance
“…Porous parameters of our modified delivery clinoptilolite systems were evaluated using N 2 -sorption analysis to assess the porous features of the hosts and pore size distribution curves to assess the pore size homogeneity and sizes. These were in close agreement with previously published studies on bimodal porous feature of the clinoptilolite [ 9 , 10 , 39 ]. Typical surface areas and pore volumes were obtained for both of our monocationic NaCLI and HCLI matrices, but as expected, these values were lower for NaCLI matrix, which explained the lower loading degree of BCNU.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Porous parameters of our modified delivery clinoptilolite systems were evaluated using N 2 -sorption analysis to assess the porous features of the hosts and pore size distribution curves to assess the pore size homogeneity and sizes. These were in close agreement with previously published studies on bimodal porous feature of the clinoptilolite [ 9 , 10 , 39 ]. Typical surface areas and pore volumes were obtained for both of our monocationic NaCLI and HCLI matrices, but as expected, these values were lower for NaCLI matrix, which explained the lower loading degree of BCNU.…”
Section: Discussionsupporting
confidence: 93%
“…Clinoptilolite is a microporous mineral component of a volcanic rock from the group of natural zeolites that has been extensively tested as a chelating agent or as an adjuvant in cancer therapy, because of its cation exchanging and chelating properties [ 6 , 7 ]. Previously published studies on clinoptilolite confirmed the bimodal porous feature of this material [ 8 , 9 , 10 ].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The synthetic zeolites were produced according to Mackinnon, Millar and Stolz 16 , granulated according to procedure described in Table 1. Clinoptilolite had a Si/Al = 4.0 (natural zeolites were reported to have a Si/Al = 3-5 11,32,33 ) while lower values of Si/Al (1.5-2.0) were measured for the synthetic zeolites ( Table 1). The zeolites were initially washed with deionized water to remove any dust from their surface and sieved to obtain the required size (1-2 mm for the synthetic zeolites and 2.5-3.5 mm for the clinoptilolite) before further tests.…”
Section: Methodsmentioning
confidence: 96%
“…Clinoptilolite is one of the predominant natural species of zeolites and has been successfully used for contaminant removal [15,44]. This mineral belongs to the heulandite group and comprises a two-dimensional channel system (a 10-ring system (0.31 nm × 0.75 nm), an 8-ring system (0.36 nm × 0.46 nm) and channels (0.28 nm × 0.47 nm) [45].…”
Section: Introductionmentioning
confidence: 99%